Additive manufacturing of SiSiC by layerwise slurry deposition and binder jetting (LSD-print). Issue 13 (October 2019) - Zocca, Andrea; Lima, Pedro; Diener, Sarah; Katsikis, Nikolaos; Günster, Jens
Abstract: The current work presents for the first time results on the Additive Manufacturing of SiSiC complex parts based on the Layerwise Slurry Deposition (LSD) process. This technology allows to deposit highly packed powder layers by spreading a ceramic slurry and drying. The capillary forces acting during the process are responsible for the dense powder packing and the good joining between layers. The LSD process can be combined with binder jetting to print 2D cross-sections of an object in each successive layer, thus forming a 3D part. This process is named LSD-print. By LSD-print and silicon infiltration, SiSiC parts with complex geometries and features down to 1 mm and an aspect ratio up to 4:1 could be demonstrated. The density and morphology were investigated for a large number of samples. Furthermore, the density and the mechanical properties, measured by ball-on-three-balls method, were in all three building directions close to isostatic pressed references.